Fracture Analysis of FRP Composites under Thermo-Mechanical Loads for Different Geometry Cutouts - Sindhu Kumar; Rone; Manish Kumar (International Journal of Fracture Mechanics and Damage Science, 2025)
Fiber-reinforced composites (FRPs) are used extensively in structural and non-structural components of the aerospace and automotive industries. To utilize these materials for structural applications, it is necessary to understand the fracture behavior of the material. In the present investigation of carbon fiber laminates, studies were carried out to understand the fracture toughness characteristics of the carbon fiber laminates with mechanical, thermal, and thermo-mechanical loadings of modes I, II, and III. The carbon composite laminate with four layers and different stacking sequences of angle-ply and cross-ply cases was investigated by considering three kinds of loadings: mechanical, thermal, and coupled thermo-mechanical loading. The finite element method was used to model the carbon composite laminate and to estimate the strain energy release rate (SERR) subjected to simply supported boundary conditions. The FE model predicted results are validated with analytical results and experimental predictions. Finite element models of laminated composite rectangular plates were modeled to determine the fracture behavior under mechanical, thermal, and combined thermo-mechanical loading. The strain energy release rate was estimated to characterize whether the crack is open or closed. Experimental results were produced by creating a composite with chopped carbon fibers and an epoxy matrix using the hand lay-up technique. The composite material with a pre-existing crack was tested for fracture toughness, and the same was simulated using ANSYS for validation. A close agreement was observed between the experimental and analytical results.
Keywords: Carbon fiber reinforced polymer (CFRP); finite element analysis (FEA); fracture toughness; strain energy release rate (SERR); thermo-mechanical loading